Preparation method of stable zirconia ceramic target material for electron beam physical vapor deposition

By stirring and pressing the raw powder of zirconia ceramic target under vacuum conditions, combined with the optimization of sintering procedure, the problems of complexity of zirconia ceramic target preparation and uneven composition are solved, and high-efficiency and low-cost zirconia ceramics are achieved. Target preparation improves the performance of thermal barrier coating.

CN119263821AActive Publication Date: 2025-01-07AVIC ARMOR TECH CO LTD

Patent Information

Application Number
CN202411314291.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-07
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing preparation methods for zirconia ceramic targets are complex and cumbersome, making it difficult to achieve industrial production, and the uneven composition leads to poor thermal barrier coating performance.

Method used

The mixed raw material powder and dispersant were added to the plasticizer under vacuum. After stirring and condensation, the ceramic slurry was formed. After pressing and molding, the particle grading and sintering procedures were adjusted to improve density and porosity. .

Benefits of technology

The preparation process is simplified, energy consumption and production costs are reduced, product production efficiency is improved, and the uniformity and performance optimization of zirconia ceramic targets are achieved through the adjustment of dispersant and particle grading.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263821A_ABST
    Figure CN119263821A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a stable zirconium oxide ceramic target material for electron beam physical vapor deposition, which comprises the following steps: uniformly stirring a zirconium oxide raw material, a plasticizer and a dispersant at high temperature without spray granulation to obtain uniformly dispersed ceramic slurry with good fluidity, cooling and solidifying to obtain an intermediate material block, and sintering to obtain the stable zirconium oxide ceramic target material for electron beam physical vapor deposition. The intermediate material block is subjected to hot melting stirring and hot pressing injection to prepare a target material blank, and then the zirconia ceramic target material is prepared by adopting a one-time high-temperature sintering method, so that the energy consumption is reduced, the production efficiency is improved, and batch production of the ceramic target material is facilitated; the particle composition of the zirconia raw materials is reasonably designed, the zirconia raw materials with coarse, medium and fine particle sizes are mixed, the porosity of the zirconia ceramic target material is properly increased, and a ceramic target material product which is uniform in component and stable in crystalline phase and meets the quality requirement is successfully prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic target material preparation, and in particular relates to a method for preparing a stable zirconia ceramic target material for electron beam physical vapor deposition. Background Art

[0002] The working principle of electron beam physical vapor deposition technology is to first evacuate the vacuum chamber of the equipment through a vacuum pump. After reaching a certain vacuum requirement, the electron gun starts to emit an electron beam, which is directly irradiated onto the evaporated material in the water-cooled crucible. The energy of the electron beam is used to heat and vaporize the material, and the material vapor is deposited on the substrate in the form of atoms or molecules to form a coating. The role of zirconia ceramic targets is to produce high-purity vapor in processes such as electron beam physical vapor deposition (EB-PVD), thereby forming a uniform, high-quality thermal barrier coating on the surface of high-pressure turbine blades of aircraft engines. As the source material of thermal barrier coatings, the quality of zirconia ceramic targets has a direct impact on the performance of thermal barrier coatings.

[0003] At present, the main preparation processes of zirconia ceramic targets are as follows: one is to ball-mill, dry, calcine and granulate the raw materials to obtain granulated powder, pre-press, re-press and debind the granulated powder to obtain ceramic target blank, and finally calcine the blank; the other is to use the secondary solid phase sintering method, mix the original fine powder raw material and the high-temperature sintered coarse powder raw material in a certain proportion, and then granulate, press and sinter. The above preparation methods are complicated and cumbersome, which is not conducive to the industrial production of zirconia ceramic targets. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides the following technical solutions:

[0005] A method for preparing a stable zirconia ceramic target for electron beam physical vapor deposition, comprising:

[0006] Step 1: Add the mixed raw material powder and dispersant to the melted plasticizer in sequence, stir evenly under vacuum conditions to obtain ceramic slurry, and cool and solidify the ceramic slurry at room temperature to obtain an intermediate block;

[0007] Step 2: Add the intermediate material block into the material cylinder of the core pressing machine, heat and melt, stir, and press to obtain a target blank;

[0008] Step 3: Load the target blank into the sagger and bury the target blank by filling powder;

[0009] Step 4: Place the sagger without target blank into a sintering furnace and sinter to obtain a zirconia target.

[0010] Furthermore, in step 1, the batching temperature is 100-140°C, the stirring speed is 20-40rpm, the vacuum degree is -0.4-0.8bar, the zirconium oxide raw material powder is added in 3 times, and each time the vacuum stirring is 1-2 hours, and finally the dispersant is added and the vacuum stirring is 1-3 hours.

[0011] Furthermore, in step 1, the raw material powder is prepared by co-precipitation method, and the components by weight percentage are: 92-90% zirconium oxide and 8-10% Y2O3 as oxide stabilizer.

[0012] Furthermore, in the zirconium oxide raw material powder of step 1, the proportion of D50 of 1 to 5 μm is 20 to 50 wt%, the proportion of D50 of 10 to 20 μm is 20 to 50 wt%, and the proportion of D50 of 20 to 50 μm is 10 to 40 wt%.

[0013] Furthermore, in step 1, the dispersant is polyethylene glycol trimethyl nonyl ether, imidazoline sulfonate or hydroxypropyl sulfonate betaine.

[0014] Furthermore, in step one, the components of the plasticizer are paraffin, beeswax, and polyethylene, with the mass proportions being: paraffin 73-76wt%, beeswax 20-22wt%, and polyethylene 2-7wt%.

[0015] Furthermore, in step 2, the material temperature is 85-105° C., and the slurry is stirred for 1-4 hours after melting, with a stirring speed of 10-40 rpm.

[0016] Furthermore, in step 2, the pressing temperature is 80-120° C., the injection pressure is 30-80 bar, the holding time is 25-50 s, the template temperature is 30-45° C., and the injection speed is 50-300 cc / sec.

[0017] Furthermore, in step three, the filling powder type is aluminum oxide or yttrium oxide.

[0018] Furthermore, in step four, the sintering system is to start from room temperature, increase the temperature to 200°C at a rate of 0.5-2°C, keep it warm for 1-8 hours, increase the temperature to 600°C at a rate of 1-3°C, keep it warm for 1-8 hours, increase the temperature to 1300-1500°C at a rate of 1-3°C, keep it warm for 1-8 hours, and then cool to room temperature with the furnace.

[0019] Beneficial effects of the present invention:

[0020] The present invention can avoid complicated granulation process and secondary solid phase sintering process, reduce energy consumption, reduce production cost and improve product production efficiency;

[0021] The dispersant used in the present invention has both hydrophilic groups and lipophilic groups. The hydrophilic end is adsorbed on the surface of the zirconium oxide particles as an anchoring group, and the long chain of the lipophilic end extends in the paraffin to prevent the mutual collision of the zirconium oxide particles. The adsorption groups of the zirconium oxide particles support each other and form a steric hindrance, which prevents the particles from approaching each other, thereby improving the uniformity of dispersion and avoiding the segregation of the zirconium oxide ceramic target due to uneven composition.

[0022] The present invention rationally designs the raw material particle size distribution so that the zirconia ceramic target material meets the density of 3.5-4.0 g / cm 3 , the quality requirement of porosity is about 30%; the particle grading has a significant influence on the porosity of zirconia ceramic target, which is mainly achieved by adjusting the size and distribution of zirconia particles. Adjusting the proportion of coarse, medium and fine particle grading can appropriately increase the porosity and reduce the density. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The drawings that constitute a part of the present invention are used to provide further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying any creative work.

[0024] Figure 1 Cutting diagram for target density uniformity test Figure 1 ;

[0025] Figure 2 Cutting diagram for target density uniformity test Figure 2 . DETAILED DESCRIPTION

[0026] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0027] Example 1

[0028] Step 1: melt the plasticizer, add the mixed raw material powder and dispersant in turn, and then stir evenly under vacuum conditions to obtain a ceramic slurry; then cool and solidify the ceramic slurry at room temperature to obtain an intermediate block; wherein,

[0029] The plasticizer is composed of paraffin wax, beeswax and polyethylene. The mass proportion is: paraffin wax 75wt%, beeswax 22wt%, polyethylene 3wt%;

[0030] The batching temperature is 120°C, the stirring speed is 30 rpm, the vacuum degree is -0.6 bar, and the zirconium oxide raw material powder is added in 3 times, and each time the vacuum stirring is 2 hours. Finally, the dispersant is added and the vacuum stirring is 2 hours.

[0031] The zirconium oxide raw material powder is prepared by a coprecipitation method, and the components by weight percentage are: 91% zirconium oxide and 9% Y2O3 as an oxide stabilizer;

[0032] In the zirconium oxide raw material powder, raw material powder with D50 of 3 μm accounts for 30wt%, raw material powder with D50 of 15 μm accounts for 40wt%, and raw material powder with D50 of 40 μm accounts for 30wt%;

[0033] The dispersant is polyethylene glycol trimethyl nonyl ether;

[0034] Step 2: Add the solidified intermediate material block into the material cylinder of the core pressing machine, heat and melt, stir, set parameters for pressing and forming, and obtain the target blank;

[0035] The material temperature is 100°C, and the slurry is stirred for 3 hours after melting, with a stirring speed of 30 rpm;

[0036] The pressing temperature was 100°C, the injection pressure was 50 bar, the holding time was 40 s, the mold plate temperature was 36°C, and the injection speed was 120 cc / sec.

[0037] Step 3: Load the target blank into the sagger and bury the target blank by filling powder; the filling powder is alumina;

[0038] Step 4: Set the temperature change program, put the sagger without target blank into the sintering furnace, and sinter the zirconia target;

[0039] The sintering system is as follows: starting from room temperature, heating up to 200°C at a rate of 1°C, keeping warm for 3 hours, heating up to 600°C at a rate of 1°C, keeping warm for 6 hours, heating up to 1450°C at a rate of 2°C, keeping warm for 2 hours, and then cooling to room temperature with the furnace. The volume density of the prepared zirconia ceramic target is 3.9 g / cm 3 , porosity 28%.

[0040] The difference between the maximum and minimum density of different parts of the target is less than 0.1g / cm 3 , target cutting schematic diagram see Figure 1 and Figure 2 , the cylindrical target is cut into three layers: upper layer, middle layer and lower layer (each layer cutting thickness is 10mm), such as Figure 1 As shown; each layer is cut in a cross shape and numbered 1 to 4, as shown Figure 2 shown.

[0041] Example 2

[0042] The difference between this embodiment and embodiment 1 is that:

[0043] In step one,

[0044] The plasticizer is composed of paraffin wax, beeswax and polyethylene. The mass proportion is: paraffin wax 74wt%, beeswax 21wt%, polyethylene 5wt%;

[0045] Batching temperature 110°C, stirring speed 40rpm, vacuum degree -0.4bar;

[0046] Among the zirconium oxide raw material powders, raw material powders with a D50 of 3 μm account for 40 wt%, raw material powders with a D50 of 15 μm account for 20 wt%, and raw material powders with a D50 of 40 μm account for 40 wt%;

[0047] In step 2, the material temperature is 105° C., and the slurry is stirred for 4 hours after melting at a stirring speed of 40 rpm.

[0048] The pressing temperature is 100°C, the injection pressure is 40 bar, the holding time is 30 s, the mold temperature is 38°C, and the injection speed is 200 cc / sec.

[0049] In step 3, the filling powder type is yttrium oxide.

[0050] In step 4, the sintering system is to start from room temperature, increase the temperature to 200°C at a rate of 0.5°C, keep it warm for 6 hours, increase the temperature to 600°C at a rate of 1°C, keep it warm for 6 hours, increase the temperature to 1500°C at a rate of 2°C, keep it warm for 3 hours, and then cool it to room temperature with the furnace. The volume density of the prepared zirconia ceramic target is 3.80g / cm 3 , porosity 29%, the difference between the maximum and minimum density of different parts of the target is less than 0.1g / cm 3 .

[0051] Example 3

[0052] The difference between this embodiment and embodiment 1 is:

[0053] In step 1, the plasticizer is composed of paraffin wax, beeswax, and polyethylene. The mass proportions are: paraffin wax 76wt%, beeswax 20wt%, and polyethylene 4wt%;

[0054] The batching temperature was 100°C, the stirring speed was 20 rpm, the vacuum degree was -0.4 bar, the zirconium oxide raw material powder was added in 3 times, each time the vacuum stirring was for 2 hours, and finally the dispersant was added and the vacuum stirring was for 3 hours;

[0055] The preparation method of zirconium oxide raw material powder is co-precipitation method, and the components by weight percentage are: zirconium oxide 90%, oxide stabilizer is 10% Y2O3;

[0056] In the zirconium oxide raw material powder, D50 of 3 μm accounts for 20wt%, D50 of 15 μm accounts for 50wt%, and D50 of 40 μm accounts for 30wt%;

[0057] The dispersant is hydroxypropyl sulfobetaine.

[0058] In step 2, the material temperature is 105°C, and the slurry is stirred for 4 hours after melting at a stirring speed of 40 rpm;

[0059] Pressing temperature 98℃, injection pressure 60bar, holding time 40s, mold plate temperature 40℃, injection speed 180cc / sec;

[0060] In step 3, the filling powder is alumina;

[0061] In step 4, the sintering system is to start from room temperature, increase the temperature at a rate of 1°C to 200°C, keep it warm for 8 hours, increase the temperature at a rate of 2°C to 600°C, keep it warm for 8 hours, increase the temperature at a rate of 3°C to 1420°C, keep it warm for 2 hours, and then cool it to room temperature with the furnace. The volume density of the prepared zirconia ceramic target is 3.45g / cm 3 , porosity 32%, the difference between the maximum and minimum density of different parts of the target is less than 0.1g / cm 3 .

[0062] Comparative Example 1

[0063] The difference between this comparative example and Example 1 is that no dispersant is added in step 1. The difference between the maximum and minimum density of different parts of the target material finally obtained in this comparative example is 0.2 g / cm 3 , the composition is uneven and does not meet the quality requirements of zirconia ceramic targets.

[0064] Comparative Example 2

[0065] The difference between this comparative example and Example 1 is that in step 1, the zirconium oxide raw material powder used is a single raw material powder with a D50 of 15 μm and a proportion of 100 wt%.

[0066] The volume density of the zirconia ceramic target finally prepared is 4.8 g / cm 3 , porosity is 24%, which does not meet the quality requirements of zirconia ceramic targets.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a stable zirconia ceramic target for electron beam physical vapor deposition, characterized in that: include: Step 1: Add the mixed raw material powder and dispersant to the melted plasticizer in sequence, stir evenly under vacuum conditions to obtain ceramic slurry, and cool and solidify the ceramic slurry at room temperature to obtain an intermediate material block; Step 2: Add the intermediate material block into the material cylinder of the core pressing machine, heat and melt, stir, and press to obtain a target blank; Step 3: Load the target blank into the sagger and bury the target blank by filling powder; Step 4: Place the sagger without target blank into a sintering furnace and sinter to obtain a zirconia target.

2. The method for preparing a stable zirconia ceramic target for electron beam physical vapor deposition according to claim 1, characterized in that: In step 1, the batching temperature is 100-140°C, the stirring speed is 20-40rpm, the vacuum degree is -0.4-0.8bar, the zirconium oxide raw material powder is added in 3 times, and each time the vacuum stirring is 1-2 hours. Finally, the dispersant is added and the vacuum stirring is 1-3 hours.

3. The method for preparing a stable zirconia ceramic target for electron beam physical vapor deposition according to claim 1, characterized in that: In step 1, the raw material powder is prepared by co-precipitation method, and the components by weight percentage are: 92-90% zirconium oxide and 8-10% Y2O3 as oxide stabilizer.

4. The method for preparing a stable zirconia ceramic target for electron beam physical vapor deposition according to claim 1, characterized in that: In the zirconium oxide raw material powder of step 1, the proportion of D50 of 1-5 μm is 20-50 wt%, the proportion of D50 of 10-20 μm is 20-50 wt%, and the proportion of D50 of 20-50 μm is 10-40 wt%.

5. The method for preparing a stable zirconia ceramic target for electron beam physical vapor deposition according to claim 1, characterized in that: In step 1, the dispersant is polyethylene glycol trimethyl nonyl ether, imidazoline sulfonate or hydroxypropyl sulfonate betaine.

6. The method for preparing a stable zirconia ceramic target for electron beam physical vapor deposition according to claim 1, characterized in that: In step 1, the components of the plasticizer are paraffin, beeswax, and polyethylene, with the mass proportions being: paraffin 73-76wt%, beeswax 20-22wt%, and polyethylene 2-7wt%.

7. The method for preparing a stable zirconia ceramic target for electron beam physical vapor deposition according to claim 1, characterized in that: In step 2, the material temperature is 85-105° C., and the slurry is stirred for 1-4 hours after melting, with a stirring speed of 10-40 rpm.

8. The method for preparing a stable zirconia ceramic target for electron beam physical vapor deposition according to claim 1, characterized in that: In step 2, the pressing temperature is 80-120° C., the injection pressure is 30-80 bar, the holding time is 25-50 s, the template temperature is 30-45° C., and the injection speed is 50-300 cc / sec.

9. The method for preparing a stable zirconia ceramic target for electron beam physical vapor deposition according to claim 1, characterized in that: In step 3, the filling powder type is aluminum oxide or yttrium oxide.

10. The method for preparing a stable zirconia ceramic target for electron beam physical vapor deposition according to claim 1, characterized in that: In step 4, the sintering system is to start from room temperature, heat up to 200°C at a rate of 0.5-2°C, keep warm for 1-8 hours, heat up to 600°C at a rate of 1-3°C, keep warm for 1-8 hours, heat up to 1300-1500°C at a rate of 1-3°C, keep warm for 1-8 hours, and then cool to room temperature with the furnace.

Citation Information

Patent Citations

  • Zirconia base ceramic target material for electron beam physical vapor deposition and preparing method of zirconia base ceramic target material

    CN106518065A

  • Preparation method of large-size zirconia ceramic target material for thermal barrier coating

    CN109721356A

  • Preparation method of large-size high-quality potassium tantalate niobate ceramic target material

    CN113956039A

  • Preparation method of high-density, high-purity and large-size ceramic target material

    CN114195513A

  • Carbon fiber molded bodies

    DE102023201375A1

Cited By

  • Zirconium oxide target material as well as preparation method and application thereof

    CN121538603A

  • Zirconia target material, method for manufacturing the same, and use thereof

    CN121538603B